HUBUNGAN POWER OTOT LENGAN DAN BAHU DENGAN HASIL KETEPATAN SMASH BULUTANGKIS PADA MAHASISWA PUTRA KELAS A PENJASKESREK ANGKATAN 2013 UNIVERSITAS RIAU - suryani, Ina; ', Saripin; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this researck is less than the maximum ability of the punch smash. this is presumably due to the lack of power arms and shoulders, this researil  was conducted to determine whether there is a connection Power Arm and Shoulder Muscles with Accuracy Results in Student Smash Badminton Men's Class A Force in 2013. The sample in this study is the Student Men's Class A Force in 2013 and bejumlah 38 people. A sampling technique that the overall population (total sampling). The instrument used in this study is testing Two Hand Medicine Ball, which aims to measure the Power arms and shoulders and then test the accuracy test Smash skills with precision punches smash that aims to measure the skills of precision punch. After that, the data is processed with statistical, normality test with lilifors test at significant level 0,05?. The hypothesis is that the alleged There is significant relationship between power relations arm and shoulder muscles with accuracy as a badminton smash. Based on analysis of test lilifors produce Lhitung (x) of 0.133 and 0.143 Ltabel, Lhitung (y) of 0.103 and 0.143 Ltabel, means Lhitung<Ltabel, then the samples come from normal populations berdristribusi. Then from the calculation of product moment correlation between the relationship of power arms and shoulders with the results of the accuracy of the smash in which rhitung (0.677)>rtabel (0.325) with consequently Ho accepted and Ha rejected. Thus there is a significant relationship between the power arm and shoulder muscles with accuracy as a smash on the male students A class of 2013 penjaskesrek University of Riau. Key Words: Arm and shoulder muscle power, precision smash